Enhancing Nutrient Recovery Efficiency through a Novel Dual-loop Aquaponic System Coupling Main Stream and Side Stream: A Review - Yongxia Zi; Dan Zeng Ke Zhu; Xinmeng He; Ang Chen; Chunjie Li (Chemical Engineering Transactions)
Aquaponics is a combination of recirculating aquaculture systems and hydroponics, which is in line with industrialization and urbanization. Typical coupled aquaponic systems use a single-loop mode to recover dissolved nutrients, while nutrient-rich aquaculture sludge is discharged, leading to a low nutrient recovery efficiency and low crop yield. Balancing the ideal conditions for aquaculture units, hydroponic units, and biofilters is difficult because of the different nutrient and environmental requirements. A decoupled aquaponic with an additional sludge treatment loop and distillation loop has been developed to overcome the shortcomings of single-loop aquaponics, but the symbiotic relationship is weakened, and the economic feasibility is challenged. In this paper, a novel dual-loop aquaponic system, coupling the main stream and side stream, is proposed for the recovery of both dissolved and solid nutrients. Nutrient conversion and nutrient losses in the main stream and side stream were discussed. The performance of aerobic and anaerobic mineralization of aquaculture sludge are compared, and a newly developed phototrophic bioconversion of aquaculture sludge based on the pre-treatment of anaerobic or aerobic solubilization is analyzed. It can be concluded that the dual-loop aquaponic system facilitates nutrient recovery from aquaculture sludge through an optimized symbiotic relationship in the main and side streams. The phototrophic bioconversion of aquaculture sludge simultaneously obtains biomass nutrients and mineral nutrients, enhancing the nutrient recovery efficiency of carbon, nitrogen, and phosphorus.